Pengaruh Brand Awareness Terhadap Brand Equity Dan Dampaknya Terhadap Keputusan Menjadi Nasabah Bank Syariah - Nur Aida (Universitas Negeri Padang, 2018)
The research is aimed to determine the effect of brand awareness on brand equity, the influence of brand awareness to the decision to become a customer and the influence of brand awareness on the decision to become customers with variable brand equity as variable interventing. The population is teachers at LPPM Walisongo, sample number is 100. The data of the questioner's dissemination tested the validity, reliability and the result is valid and reliable. Result of hypothesis test that there’s influence of brand awareness to brand equity significantly proven t-count value > t-table, there’s influence of brand awareness to decision to become customer proved t-count value > t-table and there’s significant influence of brand awareness on the decision to become a customer through brand equity variable as intervening variable, in accordance with Sobel test where the value of t arithmetic versus t table of concluded that the coefficient of mediation significant.